Regulation of aquaporin-2 in the kidney: A molecular mechanism of body-water homeostasis - Tae-Hwan Kwon; Jørgen Frøkiær; Søren Nielsen (The Korean Society of Nephrology, 2013)
The kidneys play a key role in the homeostasis of body water and electrolyte balance. Aquaporin-2 (AQP2) is the vasopressin-regulated water-channel protein expressed at the connecting tubule and collecting duct, and plays a key role in urine concentration and body-water homeostasis through short-term and long-term regulation of collecting duct water permeability. The signaling transduction pathways resulting in the AQP2 trafficking to the apical plasma membrane of the collecting duct principal cells, including AQP2 phosphorylation, RhoA phosphorylation, actin depolymerization, and calcium mobilization, and the changes of AQP2 abundance in water-balance disorders have been extensively studied. Dysregulation of AQP2 has been shown to be importantly associated with a number of clinical conditions characterized by body-water balance disturbances, including hereditary nephrogenic diabetes insipidus (NDI), lithium-induced NDI, electrolytes disturbance, acute and chronic renal failure, ureteral obstruction, nephrotic syndrome, congestive heart failure, and hepatic cirrhosis. Recent studies exploiting omics technology further demonstrated the comprehensive vasopressin signaling pathways in the collecting ducts. Taken together, these studies elucidate the underlying molecular mechanisms of body-water homeostasis and provide the basis for the treatment of body-water balance disorders.